Implementation of Internal Control System on Zakat Funds Management at Lembaga Amil Zakat Infaq dan Shadaqah Muhammadiyah (LAZISMU) - Yulian Sahri (Journal of Research in Business, Economics, and Education, 2020)
The rapid development of organizations which manage zakat shows that there needs to be an internal control implementation to minimize the chances of alms funds mishandling. The aim of this research is to assess the compliance and to evaluate the effectiveness of the internal control system on the management of alms funds at Lembaga Amil Zakat Infaq dan Shadaqah Muhammadiyah (LAZISMU) Yogyakarta Special Region according to the COSO 2013 internal control frameworks. This research uses a qualitative method with a case study approach. The research data is collected by means of interviews, observations, document inspection, and questionnaires. The research results show that the internal control system implementation on alms funds management at LAZISMU Yogyakarta Special Region is compliant with the COSO 2013 internal control frameworks, and can be categorized as sufficiently effective, with a percentage of 69.40%. This is because there are components which haven’t been fully implemented by the organization.